2021
DOI: 10.1101/2021.05.16.444367
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Dissecting the Cellular Landscape and Transcriptome Network in Viral Myocarditis by Single-Cell RNA Sequencing

Abstract: Myocarditis induced with Coxsackievirus B3 (CVB3) is commonly employed to study viral pathogenesis in mice. Although infectious virus is cleared after the acute phase, affected animals chronically develop the features of dilated cardiomyopathy, which may involve the mediation of immune and non-immune cells. To dissect this complexity, we performed single-cell RNA sequencing on heart cells obtained from healthy and myocarditic mice, leading us to note that myocarditic mice had significantly higher proportions o… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 90 publications
(178 reference statements)
0
4
0
Order By: Relevance
“…Apod is a cardioprotective gene whose expression is induced in mouse hearts during myocardial infarction and has been proposed to protect the heart against ischemic damage (Tsukamoto et al, 2013). In addition, Apod has been reported to be the most significantly upregulated gene in SARS-CoV-2-infected cardiac tissue in fatal COVID-19 cases (Brauninger et al, 2022) and has been found upregulated in a cluster of cardiac fibroblasts during Coxsackievirus B3 infection (Lasrado et al, 2022). Further studies are required to determine the specific role of Apod in cardioprotection during CHIKV infection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Apod is a cardioprotective gene whose expression is induced in mouse hearts during myocardial infarction and has been proposed to protect the heart against ischemic damage (Tsukamoto et al, 2013). In addition, Apod has been reported to be the most significantly upregulated gene in SARS-CoV-2-infected cardiac tissue in fatal COVID-19 cases (Brauninger et al, 2022) and has been found upregulated in a cluster of cardiac fibroblasts during Coxsackievirus B3 infection (Lasrado et al, 2022). Further studies are required to determine the specific role of Apod in cardioprotection during CHIKV infection.…”
Section: Discussionmentioning
confidence: 99%
“…One limitation of this study is that bulk population measurements might occlude local cellular effects. Single-cell technologies have been recently applied to the study of cardiac tissue, providing the opportunity to study viral myocarditis at single-cell resolution (Lasrado et al, 2022). Further studies focusing on spatial single-cell transcriptomics on CHIKV-infected cardiac tissue may help elucidate the role of the local inflammation in CHIKV clearance.…”
Section: Discussionmentioning
confidence: 99%
“…In experimental autoimmune myocarditis (EAM) model at different phases, scRNA-seq identified 26 cell subtypes among 34665 cells and found that Hif1a contributes to the inflammatory response mainly through the regulation of macrophage and T-helper 17 cells [17]. A recent study revealed that myeloid cells, T cells, and fibroblasts play a critical role in the cytotoxic functions and inflammation and immune response in viral myocarditis [18]. Pathogenic immune cell subsets in checkpoint inhibitor-induced myocarditis model [19] and peripheral immune landscape in BNT162b2 mRNA vaccine-induced myocarditis model [20] were described by scRNA-seq.…”
Section: Discussionmentioning
confidence: 99%
“…Yet, these ensemble-level approaches do not capture the cellular and spatial heterogeneity of host response to infection. scRNA-seq has recently been used to study Coxsackievirus B3 (CVB3)-induced myocarditis in a mouse model 39 . Lasrado et al report inflammatory phenotypes of myeloid cells, the role of fibroblasts in remodeling and inflammation, and the role of cytotoxic T-cells in CVB3-induced myocarditis.…”
Section: Discussionmentioning
confidence: 99%